Symbol Cyclic-Shift Equalization Algorithm-A CP-Free OFDM/OFDMA System Design - Liu, Xiqing; Chen, Hsiao-Hwa; Chen, Shuyi; Meng, Weixiao (IEEE transactions on vehicular technology, 2017)
The use of cyclic prefix (CP) allows all existing orthogonal frequency-division multiplexing or multiple access (OFDM/OFDMA) systems to realize high-data-rate transmission in frequency-selective fading channels at the expense of losses in spectrum efficiency, energy efficiency, and transmission rate (SET). This paper proposes a CP-free OFDM/OFDMA design. Unlike traditional OFDM/OFDMA systems, the proposed CP-free OFDM/OFDMA does not insert CPs between symbols at the transmitter side. The neighboring symbols in frequency-selective fading channels will be overlapped at a receiver, and decision feedback equalization (DFE) is performed before FFT operation for intersymbol interference (ISI) removal. After DFE, each symbol consists of multipath returns with different linear shifts (LSs), which may result in intercarrier interference (ICI). Therefore, the output symbols from the DFE will be sent to a CP restoration unit for LS-to-cyclic-shift (CS) conversion. We call this a CP-free OFDM/OFDMA system symbol CS equalizing OFDM/OFDMA (SCSE-OFDM/OFDMA), whose system design is introduced in detail in this paper. We will show that SCSE-OFDM/OFDMA offers a much higher SET than traditional OFDM/OFDMA systems in frequency-selective fading channels.